The Impact of Differentiated Instruction on Students' Critical Thinking Skills in Secondary Science Classrooms: A Quasi-Experimental Study - Baso Intang Sappaile; Bahmid Hasbullah; Wahdah; Kaso Mustamin; Dodi Sukmayadi (International Journal of Educational Research Excellence (IJEREC), 2027)
Critical thinking is a cornerstone of 21st-century science education, yet traditional one-size-fits-all pedagogy often fails to cultivate it among diverse Indonesian secondary learners. This mixed-methods quasi-experimental study examined the impact of differentiated instruction (DI) on students’ critical thinking skills in secondary science. Participants were 70 eighth-grade students from a public junior high school in Yogyakarta, assigned to an experimental group (n=35) receiving DI based on readiness, interest, and learning profile over eight weeks, and a control group (n=35) receiving conventional instruction. Critical thinking was measured using a validated essay test aligned with Facione’s framework (interpretation, analysis, evaluation, inference, explanation, self-regulation). Quantitative analysis via ANCOVA revealed a significant large effect of DI on post-test scores (F(1,67)=48.62, p<.001, η²p=.42) after controlling for pre-test. Qualitative data from classroom observations and semi-structured interviews with 10 students and 2 teachers revealed four themes: heightened intellectual engagement, personalized scaffolding, collaborative meaning-making, and implementation challenges. Integration of findings demonstrated that DI fosters critical thinking by honoring learner variability, promoting active sense-making, and providing tiered cognitive demands. The study underscores DI as a viable pedagogical framework for nurturing higher-order thinking in Indonesian science classrooms, while highlighting the need for sustained professional development to address practical constraints